Respuesta :

The solution is [tex]x = 2 \text{ and } y = \frac{1}{2}[/tex]

Solution:

Let us assume,

[tex]a = \frac{1}{x}\\\\b = \frac{1}{y}[/tex]

Given system of equations are:

[tex]\frac{2}{x} - \frac{3}{y} = -5[/tex]

[tex]\frac{4}{x} + \frac{6}{y} = 14[/tex]

Rewrite the equation using "a" and "b"

2a - 3b = -5 ------------ eqn 1

4a + 6b = 14 -------------- eqn 2

Let us solve eqn 1 and eqn 2

Multiply eqn 1 by 2

2(2a - 3b = -5)

4a - 6b = -10 ------------- eqn 3

Add eqn 2 and eqn 3

4a + 6b = 14

4a - 6b = -10

( - ) --------------------

8a = 4

[tex]a = \frac{4}{8}\\\\a = \frac{1}{2}[/tex]

Substitute a = 1/2 in eqn 1

[tex]2(\frac{1}{2}) -3b = -5\\\\1 - 3b = -5\\\\3b = 6\\\\b = 2[/tex]

Now let us go back to our assumed values

Substitute a = 1/2 in assumed values

[tex]a = \frac{1}{x}\\\\\frac{1}{2} = \frac{1}{x}\\\\x = 2[/tex]

Substitute b = 2 in assumed value

[tex]b = \frac{1}{y}\\\\2 = \frac{1}{y}\\\\y = \frac{1}{2}[/tex]

Thus the solution is [tex]x = 2 \text{ and } y = \frac{1}{2}[/tex]

ACCESS MORE
EDU ACCESS
Universidad de Mexico